KETAHANAN PANGAN RUMAH TANGGA DI KABUPATEN CIAMIS - Asep Herdiana; Dwidjono Hadi Darwanto; Jangkung Handoyo Mulyo (Universitas Sebelas Maret, 2014)
Food security at the national or regional level does not ensure food securityat the household and individual level. Benchmark attainment of food security at thehousehold level is ensuring the physical and economic accessibility to food. Thisresearch aims to determine the household food security level in the district of Ciamisand the factors that influence it by using table analysis and ordinal probit regressionmodels. Data used in this study is National Social Economic Survey (SUSENAS) 2012from Central Beaureu of Statistic (BPS). In 2012, there are still households who cannot stand the food, this is indicated by the distribution of households by level ofhousehold food security, it can be seen from the distribution of households by level offood security based on Jonsson and Toole method are: vulnerable households 530(54.08%), household food security 264 (26.94 %), insecure households 124 (12.65 %)and households less food 62 (6.33 %), while according to the modified method are:vulnerable households 592 (60,41%), household food security 264 (26.94 %) andinsecure households 124 (12.65 %). Householdincome,household head education,household size, ownership of rice, food base animal price and cooking oils price werefound to be significant determinants of household food security level in the study area. Ketahanan pangan di tingkat nasional atau regional belum tentu menjaminketahanan pangan di tingkat rumah tangga atau individu. Tolok ukur pencapaianketahanan pangan rumah tangga adalah terjaminnya akses fisik dan ekonomi terhadappangan.Penelitian ini bertujuan untuk mengetahui ketahanan pangan rumah tangga diKabupaten Ciamis dan faktor yang mempengaruhinya, menggunakan analisis regresimodel ordinal probit.Data yang digunakan bersumber dari data SUSENAS 2012 dariBPS.Pada tahun 2012, di Kabupaten Ciamis masih terdapat rumah tangga yang tidaktahan pangan.Hal tersebut terlihat dari distribusi rumah tangga menurut tingkatketahanan pangan. Berdasarkan metode Jonsson dan Toole terdapat rumah tanggarentan pangan 530 (54.08%), rumah tangga tahan pangan 264 (26.94 %), rumahtangga rawan pangan 124 (12.65 %) dan rumah tangga kurang pangan 62 (6.33 %),sedangkan menurut modifikasi metode Jonsson dan Toole terdapat rumahtanggarentan pangan 592 (60,41%), rumah tangga tahan pangan 264(26.94 %) dan rumahtangga rawan pangan 124 (12.65 %).Pendapatan rumah tangga, lama pendidikankepala rumah tangga, jumlah anggota rumah tangga, jumlah beras yang tersedia untukdikonsumsi, harga kelompok bahan pangan hewani dan kelompok pangan minyak danlemak berpengaruh terhadap tingkat ketahanan pangan rumah tangga.